2021
DOI: 10.1002/ajmg.a.62601
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in fragile X syndrome: Cross‐sectional analysis of a large clinic‐based cohort

Abstract: Fragile X syndrome (FXS), the leading cause of inherited intellectual disability and autism spectrum disorder, is associated with multiple neurobehavioral abnormalities including sleep difficulties. Nonetheless, frequency, severity, and consequences of sleep problems are still unclear. The Fragile X Online Registry with Accessible Research Database (FORWARD-version-3), including Clinician Report and Parent Report forms, was analyzed for frequency, severity, relationship with behavioral problems, and impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Overall, our results suggest sleep dysfunction is common among those with WSS, in line with recent cross-syndrome investigations involving rare genetic disorders including Smith-Magenis, Fragile X, Angelman, Prader-Willi, Cornelia de Lange, CHARGE, Williams, KAT6A, and Kabuki syndromes (Angriman et al, 2015;Kaufmann et al, 2017;Agar et al, 2021;Budimirovic et al, 2021;Smith and Harris, 2021;Veatch et al, 2021;Rapp et al, 2022). Within our sample, sleep apnea was reported at a relatively high rate (40.90%) compared to the recent study by Sheppard et al (2021) (24.7%).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our results suggest sleep dysfunction is common among those with WSS, in line with recent cross-syndrome investigations involving rare genetic disorders including Smith-Magenis, Fragile X, Angelman, Prader-Willi, Cornelia de Lange, CHARGE, Williams, KAT6A, and Kabuki syndromes (Angriman et al, 2015;Kaufmann et al, 2017;Agar et al, 2021;Budimirovic et al, 2021;Smith and Harris, 2021;Veatch et al, 2021;Rapp et al, 2022). Within our sample, sleep apnea was reported at a relatively high rate (40.90%) compared to the recent study by Sheppard et al (2021) (24.7%).…”
Section: Discussionsupporting
confidence: 90%
“…Only those with adequate saliva collection were included in this study. Those receiving any kind of medical treatment and those with attention-deficit hyperactivity disorder and specific genetic syndromes, such as fragile X, were excluded from the study as these disorders can associate impaired sleep themselves ( 25 , 31 , 32 ). Children and adolescents with intellectual disabilities were included.…”
Section: Methodsmentioning
confidence: 99%
“…Other comorbid conditions of FXS reported in our study are consistent with many studies, some being associated with other major findings. For example, Budimirovic et al ( 2022 ) focused on cooccurring conditions associated with the presence of sleep problems in patients with FXS. They found that sleep difficulties were associated with behavioral problems such as irritability or aggression, anxiety, and hyperactivity; all conditions reported in our data set.…”
Section: Discussionmentioning
confidence: 99%